Diverse paradigms and stories: mapping `mental illness` in athletes through meta-study - Vargas, M. L. F. P.; Papathomas, A.; Williams, T. L.; Kinnafick, F.-E.; Rhodes, P. (International Review of Sport and Exercise Psychology, 2024)
This meta-study systematically appraises and synthesizes research into athletes` experiences of mental illness. Our critical review of 37 studies conformed to the meta-study structure of meta-theory, meta-method, and meta-data analysis. We also produced a meta-synthesis of findings to deliver new insights into athlete mental illness. Athlete accounts of mental illness pertained to experience of the following: depression, eating disorders, gambling addiction and substance-related disorders (alcohol and drugs). Following a critical interrogation of original articles` theory, method, and findings, we noted a general lack of methodological coherence (congruence between philosophical stance, theoretical position, and methodology). Through the process of a thematic synthesis, we developed 4 new themes: origins of certainty and ambiguity, a gradual sense of decline, mental illness as a threat to identity, and constructing recovery stories. Athletes drew upon dominant illness discourses to construct mental illness and recovery experiences. Our results provide us with an understanding of how mental illness and recovery were experienced within an elite sport involvement. We recommend future research embraces more diverse methodologies and authors ensure a strong alignment between guiding philosophies and methodological approach.